Photoacoustics for listening to metal nanoparticle super-aggregates. Issue 16 (9th July 2021) - Li Voti, Roberto; Leahu, Grigore; Sibilia, Concita; Matassa, Roberto; Familiari, Giuseppe; Cerra, Sara; Salamone, Tommaso Alberto; Fratoddi, Ilaria
Abstract : The detection of a photoacoustic signal allows listening to both absorption and scattering phenomena generated by three-dimensional self-assembled super-aggregates. Quantitative size and filling factor morpho-parameters was extrapolated by absorption and scattering spectra. Abstract : Photoacoustic signal detection has been used to build a new strategy to determine the mesoscale self-assembly of metal nanoparticles in terms of size distribution and aggregate packing density (metal nanoparticle filling factor). A synergistic approach integrating photoacoustic signal and theoretical studies, validated by conventional light scattering and electron microscopy techniques, allows us to obtain a well-defined morphological interpretation of nanoparticle-based super-aggregates. By pumping light in a complex system, the acousto-thermal effect was listened to, providing information on the aggregation phenomena. Super-aggregates of covalently interconnected silver nanoparticles (AgNPs) functionalized with an organometallic dithiol are identified in solution, as a proof of concept for the versatility of the photoacoustic approach. According to our results, tiny AgNPs (size less than 10 nm) assembled into a 3D-network of super-aggregates (SA-AgNPs) with sizes in the range 100–200 nm and a filling factor in the range of 30–50%. Low-cost, rapid, and easy photoacoustic measurement in the low frequency range (less than 100 Hz) was revealed to be an innovative method to characterize the fundamental structure/property correlation of metal nanoparticle super-aggregates. This morpho-optical approach, which uses the absorption and scattering properties of nanoparticles in the liquid phase, opens new perspectives for advanced biomedical and structural applications.